Imperfect Information in Menstrual Health and the Role of Informed Choice. (February 2019) - Mahajan, Tanya
This article explores how imperfect information and the culture of silence around menstruation have shaped the menstrual hygiene product market. It is generally considered that the use of sanitary napkins is equivalent to hygiene. This view is critically evaluated in light of evidence. In a highly competitive market, materials used in sanitary napkin products have evolved significantly. Policymakers and regulators need to be informed about the nature of products entering the Indian market and their implications on women's health and cost to the environment. The menstrual hygiene market now offers some less-known innovations such as menstrual cups, reusable cloth pads and compostable sanitary napkins that could offer a more sustainable direction to the industry. However, they also have their own barriers to access and use. Given the increasing choice available in the market and potential for accessing information, it has become pertinent that relevant stakeholders—such as women, government officials and the media—are made aware of the basket of options for menstrual hygiene management. Field experiments done to this end indicate that informed choice will automatically ensure that cost to women's health and the environment is minimised.